Transpalpebral Approach "Eyelid Incision" for Surgical Treatment of Intracerebral Aneurysms: Lessons Learned During a 10-Year Experience. Issue 3 (14th August 2019) - Mao, Gordon; Gigliotti, Michael; Aziz, Khaled; Aziz, Khaled
Abstract: BACKGROUND: The classic pterional, pretemporal, and orbitozygomatic approaches achieve large areas of exposure with easy maneuverability. In select cases (eg, some anterior circulation aneurysms), the minimally invasive fronto-orbital craniotomy can yield adequate exposure that must be balanced with its risk of frontalis injury. OBJECTIVE: To detail a 10-yr experience using the transpalpebral approach, characterized by an incision whose camouflage is the natural eyelid crease, notably the effectiveness and outcomes of this exposure for anterior circulation aneurysms. METHODS: In this retrospective review, 82 patients with 88 aneurysms underwent a supraorbital frontal minicraniotomy via the eyelid incision performed by a single neurosurgeon and closure by an oculoplastic surgeon (2007-2016). Incision of the orbiculi oculi developed a plane between the muscle and orbital septum superiorly. Outcomes recorded included aneurysm occlusion or residual, treatment modality (clipping/wrapping), postoperative hemorrhage or stroke, postoperative wound healing, and overall cosmesis. RESULTS: Of 85 (97%) aneurysms treated by clipping, postoperative and follow-up imaging showed complete obliteration in 81 (95%) aneurysms and residuals in 4 (5%). Cosmetic outcomes for the eyelid incision were excellent: 81 (99%) patients noted excellent wound healing at follow-up and no scarring; 1 patient developed significant temporalis wasting and upper eyelid scarring after posterior communicating artery aneurysm clipping. Overall, 13 minor and 8 major complications affected 19 patients. CONCLUSION: Our findings confirm the versatility of the eyelid supraorbital frontal minicraniotomy for common anterior circulation aneurysms. This large series found that postoperative complication risks were similar to traditional techniques and cosmetic results were excellent.